2002
DOI: 10.1016/s0022-5347(05)64625-3
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study Of 22.5 mg. La-2550: A New Subcutaneous Depot Delivery System For Leuprolide Acetate For The Treatment Of Prostate Cancer

Abstract: LA-2550 (22.5 mg. depot) produced and maintained safe and effective suppression of serum testosterone to well below the medical castrate level of 50 ng./dl. or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 18 publications
8
47
2
Order By: Relevance
“…The frequency of injection-site-related complaints – typical for subcutaneous injectable products – in this real-life MANTA study was comparable to what was observed in the clinical trials [6, 7]. However, in the current study, physicians were asked specifically to describe all complaints related to injection of the LA depot formulation (pain, hematoma, tumor flare, etc.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The frequency of injection-site-related complaints – typical for subcutaneous injectable products – in this real-life MANTA study was comparable to what was observed in the clinical trials [6, 7]. However, in the current study, physicians were asked specifically to describe all complaints related to injection of the LA depot formulation (pain, hematoma, tumor flare, etc.…”
Section: Discussionsupporting
confidence: 70%
“…With regard to safety and tolerability, fewer patients experienced TEAE in daily clinical practice than in the clinical trials with the 1- and 3-month LA depot formulation [6, 7]. The frequency of injection-site-related complaints – typical for subcutaneous injectable products – in this real-life MANTA study was comparable to what was observed in the clinical trials [6, 7].…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…For the in vitro studies, the drug is combined with the polymer solution and small drops of the mixture (about 50 mg) are added to phosphate-buffered saline solution. The receiving fluid is replaced at selected times with fresh solution, and the removed phosphate buffer saline solution is analyzed for drug concentration using a variety of analytical methods [13].…”
Section: Fig 1: Controlled Release By Atrigel Systemmentioning
confidence: 99%